(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
The surgical treatment of critical-sized bone defects with complex three-dimensional geometries is a challenge for the treating surgeon. Additive manufacturing such as 3D printing enables the production of highly individualized bone implants, meeting the shape of the patient’s bone defect and including a tunable internal lattice structure [1]. Although technological progress for 3D printing of implants has been achieved, clinically relevant work flows are not yet established in trauma surgery. In this study, we showcase the design process for patient specific implants with critical-sized tibia defects. The ideal implant design has to provide mechanical stability, as well as material and design related features to support the biologization of the implant. Finally, the surgical process to fill the bone void with the 3D printed construct is an essential part of the design process. Using different software packages, defects are modeled from CT datasets and filled with different lattice structures to achieve this goal. Clinical cases of patients with critical bone defects were chosen and Brainlab[2] software was used for segmentation of CT data to generate 3D models of the defects. The specified volume was then filled with Voronoi, Gyroid, and NaCl crystal lattice structures. Variations in pore size were accomplished by adjusting unit cell size and wall/beam thickness, the designed implants and test bodies were printed from resin (clear V4, SLA printer Form 3). Test bodies were compression tested to gather data for subsequent finite element analysis of the designed implant. In this proof-of-principle study customized tibia implants were successfully generated and printed as a model implant from resin. Further studies will include more patient datasets to refine the workflows and digital tools for a broader spectrum of bone defects. Additional mechanical testing and finite element analysis will be used to improve prediction of mechanical properties and to further evaluate different lattice structures for their mechanical properties. Besides mechanical aspects, biological suitability plays a major role and is investigated with biocompatible biomaterials.